2018
DOI: 10.3399/bjgp18x699749
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ reasons for consulting a GP when experiencing a dental problem: a qualitative study

Abstract: BackgroundThere are approximately 380 000 dental consultations in UK general practice every year.AimTo explore the reasons why patients may consult a GP rather than a dentist when experiencing problems with their teeth or gums.Design and settingA qualitative semi-structured interview study with adults who had consulted a UK GP with a dental problem in the previous 12 months.MethodParticipants were recruited via print and social media; internet adverts; HealthWise Wales, the Welsh national population research c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…In total, HWW has facilitated the recruitment of 43 826 participants to 15 different studies to date, with many of the 21 779 registrants taking part in multiple studies. Results from these studies are now being published including, for example, an analysis of patients’ reasons for consulting a general practitioner when they had a dental problem 15. Links to all publications that have used HWW to recruit participants will be included on the project website.…”
Section: Research Activitiesmentioning
confidence: 99%
“…In total, HWW has facilitated the recruitment of 43 826 participants to 15 different studies to date, with many of the 21 779 registrants taking part in multiple studies. Results from these studies are now being published including, for example, an analysis of patients’ reasons for consulting a general practitioner when they had a dental problem 15. Links to all publications that have used HWW to recruit participants will be included on the project website.…”
Section: Research Activitiesmentioning
confidence: 99%
“…In Australia, registered nurses practice in hospitals, residential care facilities and long‐term care institutions, managing medically compromised and elderly people as well as individuals with disabilities 2 . The high utilization of non‐dental healthcare services for oral health‐related concerns, 7,8 including those provided by registered nurses, 9,10 further highlights their role in collaborative oral health care.…”
Section: Introductionmentioning
confidence: 99%
“…Holzinger et al also reported GPs' frustration relating to requests from GDPs for advice on anticoagulant therapy and dose adjustment for dental procedures, suggesting that this practice is widespread [23]. Cope et al found UK GPs to be equally frustrated when faced with prescribing antibiotics to treat dental pain (particularly given concerns regarding antimicrobial resistance) [43].…”
Section: Discussionmentioning
confidence: 99%